Community-Based Surveys for Determining the Prevalence of HIV, Chlamydia, and Gonorrhoea in Men Having Sex with Men in Hong Kong. (9th April 2013) - Wong, H. T. H.; Wong, K. H.; Lee, S. S.; Leung, R. W. M.; Lee, K. C. K.
Abstract : Background . Community sampling of men having sex with men (MSM) for human immunodeficiency virus (HIV) and sexually transmitted infections prevalence studies poses challenges in view of problems in logistics and the hidden nature of MSM population. Methods . MSM in Hong Kong were recruited through social venues and the Internet. All participants were invited to complete a behavioural questionnaire and submit a urine specimen for HIV, Chlamydia, and gonorrhoea testing. Results . Totally, 994 MSM were recruited. No differences between venue and online-recruited respondents were identified regarding their demographics and infection status. The prevalence of HIV, Chlamydia, and gonorrhoea was 3.6% (95% CI: 2.6–5.0%), 4.7% (95% CI: 3.6–6.2%), and 0.2% (95% CI: 0.1–0.7%), respectively. Of all HIV cases, only 8.3% were aware of the infection; reflecting newly infected MSM were probably overrepresented. Some 58.3% had had HIV test within the past year, and 11.1% had CT/NG coinfection. HIV infection was associated with group sex [aOR: 2.67 (1.03–6.92)], receiving money for anal sex [aOR: 4.63 (1.12–19.18)], and unprotected anal sex with nonregular partners [aOR: 3.047 (1.16–8.01)]. Conclusion . Difference between venue- and online-recruited MSM was observed. A combination of sampling methods is complementary for epidemiology purpose. Overall, risk behaviours practised by undiagnosed HIV-positive MSM remains a cause for concern.